PENGARUH PERTUMBUHAN PERUSAHAAN, OPINI AUDIT TAHUN SEBELUMNYA, AUDITOR SWITCHING DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2017) - Nadhif, Cahya Fauzan Awdi; Andreas, Andreas; Eka, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Responsibility of auditors currently do not only focus on assessing the fairness of financial statements and detecting fraud, but also information that is not limited in the things revealed in the financial statements, such as disclosure of information about the existence and continuity of corporate entities. This is due to the demands of the shareholders to the auditor ti provide early warning about the prospect of a company as consideration before deciding on an investment decision. In this study, we attempt empirically to examine the effect of Growth Companies, Previous Year Audit Opinion, Auditor Switching And Institutional Ownership On Receiving Of Going Concern Audit Opinion on receiving a going concern audit opinion of a compaany. Research sample amounts to 17 companies selected with purposive sampling method, with observation period of 5 years.The date used were secondary data. The data that used in this research is audited financial statements that published by manufacturing companies listed at Indonesian Stock Exchange from 2013-2017. The method of analysis used logistic regression method. The result of logistic regression using SPSS that,previous year audit opinion and institutional ownership were significant with going concern audit opinion. But, variables growth of companies and auditor switching weren’t significant with going concern audit opinion.Keyword : Growth Companies, Previous Year Audit Opinion, Auditor Switching, Institutional Ownership, Receiving Of Going Concern Audit Opinion